Proposed Improvement of Facility Layout in Production Area in Ud. Arshaindo Using the From To Chart (FTC) Method - Abdul Azis Alghushan; Mochammad Nuruddin; Said Salim Dahda (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Small and medium industry engaged in fast food. Currently, the layout of the facilities at the production site is experiencing problems related to the distance of material movement. This study aims to redesign the layout of the facility and make suggestions to the trade business to minimize material movement to make it more comfortable and efficient. The method used in the process of redesigning the layout of the facility at UD. ARSHAINDO is to use the FTC (From To Chart) method. From To Chart is a method that can help to solve problems then described in more detail by going through several stages of completion to the maximum point. The results obtained from the From To Chart calculation with a total distance between departments of 36 meters (proposed layout), while the distance applied to UD. ARSHAINDO currently has a distance between departments of 56 meters (initial layout), therefore the proposed layout design has minimized the material transfer distance between departments by 20 meters so that it can produce a maximum layout and the production process is more efficient in terms of the distance between previous departments